Association of epidural labor analgesia with maternal and neonatal outcomes in women with preeclampsia: a propensity score-matched single-center retrospective cohort study - Xi-Zhu Wu; Tuan-Fang Fang; Yi-Han Zheng; Su-Jing Zhang; Yi Xie; Xiang Gao; Guo-Lin Lu (BMC Pregnancy and Childbirth)
Abstract Background Epidural labor analgesia (ELA) is widely and safely used for labor pain relief. However, it remains unclear whether ELA affects maternal and neonatal outcomes in women suffering from preeclampsia. Methods This study reviewed the medical records of women with preeclampsia at ≥ 28 weeks of gestation between January 2015 and December 2020. The medical records of women were divided into ELA and no analgesia (NA) groups. The primary endpoint was the cesarean section (CS) rate. Secondary endpoints included hypotension, operative vaginal delivery, fetal distress, neonatal intensive care unit admission, and complications. Using multivariate logistic regression analysis and propensity score matching (PSM), the association between ELA and maternal and neonatal outcomes was examined. Results A total of medical records of 686 women were enrolled, with 242 (35.3%) receiving ELA. Of these, 126 (18.4%) had a higher incidence of CS in the ELA group than in the NA group (22.7% vs. 16.0%, P = 0.020). Multivariable analysis indicated greater risks of CS [adjusted Odds Ratio (aOR) = 1.71; 95% CI, 1.07–2.74; P = 0.025] and operative vaginal delivery (aOR = 2.810; 95% CI, 1.379–5.725; P = 0.004) in the ELA group than that of NA group. In the PSM, ELA did not increase the risk of CS (aOR = 1.56; 95% CI, 0.97–2.52; P = 0.067) and OVD (aOR = 2.048; 95% CI, 0.936–4.484; P = 0.073). The secondary endpoints showed no significant differences between the two groups. Conclusion The study indicates an association between ELA and maternal and neonatal outcomes, supporting the safety of ELA in this population.